Penerapan Bot Telegram untuk Sistem Monitoring Jaringan Intranet Daerah di Instansi Pemerintahan - Wahyu, Muhamamad; Fitrani, Arif Senja; Hindarto, Hindarto (Fakultas Teknik Universitas Hamzanwadi, 2024)
Currently, the internet has become a basic need in the process of providing information and knowledge. Public, government and private services compete with each other in the use of information technology, which is expected to support employee performance and service. Therefore, human resources are needed who not only master material aspects, but also have adequate capacity and ability to apply and develop information in all fields. The use of this monitoring system is very necessary for the sidoarjo communicarions and information services departement and institutions that operate in the network sector and also have a fairly broad and complex customer coverage. Problems that often occur are slow internet connections, broken network cables, damaged network devices, etc. At that time, a network monitoring system was needed as a system that could detect when the network connection was lost. The research method used in this research is experimentation, namely a category of research that aims to find the cause and effect situation of a phenomenon. Therefore, this research is to investigate cause and effect, in accordance with previous conditions. From the results of the tests carried out, Mikrotik succeeded in sending notification messages in real time to the Telegram bot, with an average response time of 1 second in each condition. Router and Telegram will detect and send real-time message notifications to administrators if the internet connection status changes from off to active or vice versa